Inverse association between triglyceride–glucose index and maximal oxygen uptake in US young and middle-aged population: a cross-sectional study - Zhang, Bin; Lai, Junxing; Li, Dan; Li, Yongfeng; Wang, Peng; Cai, Shangan; Ren, Qiang; Li, Dong (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe triglyceride–glucose (TyG) index has been linked to impaired cardiovascular fitness (CVF). However, the available evidence regarding the direct relationship between the TyG index and maximal oxygen uptake (VO2max) is limited. This study aims to investigate the association between the TyG index and VO2max.MethodsWe conducted a retrospective cross-sectional study involving 3,571 participants who completed a CVF examination as part of the National Health and Nutrition Examination Survey (NHANES) 1999–2004. Data on triglycerides, glucose, and VO2max were collected from all participants. The TyG index was calculated using the formula: Ln[triglyceride (TG)(mg/dl) × fasting plasma glucose (FPG)(mg/dl)/2]. Linear regression analysis was utilized to substantiate the research objectives.ResultsThe complex sampling design and mobile examination center sample weights were considered. In multivariable linear regression analyses, each 1 unit increase in the TyG index was associated with a decrease in VO2max [β = −1.24, 95% CI (−1.97, −0.51), p = 0.002] when expressed as a continuous variable, independent of confounders. The TyG index was converted into a categorical variable based on four quartiles. Compared with the lowest TyG quintile (Q1: 6.750–7.887), the fully adjusted β for Q4 (8.672–12.481) was −1.91 (95% CI: −3.24, −0.57, p < 0.007). A significant interaction (p = 0.007) between sex and the TyG index for VO2max was found in the population using subgroup analysis. The results of the sensitivity analysis remained stable. Mediation analysis showed the direct effect of the TyG index was −1.467 (−2.019, −0.948), with a total effect of −1.813 (−2.377, −1.286). The mediation effect of diastolic blood pressure (DBP), white blood cell count (WBC), and C-reactive protein (CRP) was −0.389 (−0.526, −0.268), −0.308 (−0.432, −0.177), and −0.252 (−0.453, −0.135), respectively. HGB was found to exert a suppressing effect on the relationship between the TyG index and VO2max, with a value of 1.469 (1.252, 1.702). The p-values for all the above effects were <0.05.ConclusionsIn the US young and middle-aged population, the TyG index was significantly adversely associated with VO2max levels. Females may exert an interaction on TyG. Evidence supported DBP, WBC, and CRP as intervening variables through which the TyG index exerts its influence on VO2max. HGB may overrule the potential inverse association between the TyG index and VO2max.NCHS IRB/ERB Protocol Number: Protocol #98-12.